Customer Preferences for Financing Products (Mudharabah, Musyarakah and Murabahah) of Bank Muamalat Indonesia Banda Aceh Branch - Hajriyanti, Rahmi; Imilda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
It is considered important to research customer preferences when using sharia financial instruments (mudaraba, musharaka, muravaha). This is not only a management consideration for Islamic banks, but is also critically needed in efforts to self-determine marketing guidelines for Shariah financial products. The purpose of this study is to find out how customer preferences for Islamic financial products at Bank Muammalat contribute, whether there are differences in customer preferences based on the characteristics of financial products, and what characteristics of Islamic financial products. is to clarify whether has a more dominant influence. Customer's decision whether or not to use this bank's loan product. The respondents were 65 customers of Mudaraba, Musharaka and Murabaha financial products of Bank Muamalat Indonesia Banda Aceh branch. Data collection was carried out by distributing questionnaires. Additionally, data were analyzed with nonparametric statistical tools using the Mann-Whitney method (U test). As a result, customers' preferences in availing Mudaraba, Musharaka and Murabaha financial products of Muamalat Bank Banda Aceh Branch are as follows: We found that it consists of public understanding, public information, and customer environment. Existence. Customer environmental factors are very important preference factors compared to other indicators. Based on statistical tests, Ho1, Ho2, Ho3, and Ho4 are accepted because we know that differences in gender, age, marital status, and education level do not make a difference in preference for the three financial instruments. Hypotheses Ha1, Ha2, Ha3, Ha4 are rejected. Conversely, differences in employment and median monthly income actually lead to differences in customer preferences for financial products. (Ha5, Ha6 are accepted and vice versa; Ho5, Ho6 are rejected). The conclusions drawn from this study are that customer preferences in using Islamic financial products are related to economic benefits, bank location, financial security, adherence to beliefs, profit sharing concept, religious understanding, public information, It is the customer environment. Among these preferences, the customer's environmental factor is the dominant preference compared to other factors